Estratégias para aumentar a recuperação de nitrogênio em pessegueiro - Paula, Betania Vahl de (2019)
The peach is a fruit appreciated in the world because when consumed in natural it has a sweet and pleasant flavor and appearance of reddish yellow color. But also, it can be consumed in jams and candies. Therefore, the properties, municipality, states, and countries are produced and generate positive economic and social impact. However, as the peach trees (Prunus persica) are cultivated in soils with the most diverse organic matter content, in some of them, the amount of native N available does not supply the demand of the plants for the nutrient. Therefore, it becomes necessary to apply nitrogen sources (N), especially in fertilization of growth and maintenance. However, the percentage of N recovered by the peach tree is often low, which can decrease productivity and negatively affect fruit composition. Therefore, it is necessary to define strategies to increase the recovery of N by the peach tree, such as the selection of rootstocks or cultivars more efficient in nutrient absorption, the choice of N sources more suitable for young peach trees and the best times of application of N in adult peach trees in production. The overall objective of the study was to develop strategies to increase N recovery in young peach trees and in production. In study 1 we tried to develop a methodology that allowed to determine the kinetic parameters of N absorption in peach trees. For this, 7, 15 and 30 days of exhaustion of internal nutrient reserves were tested in peaches grown in CaSO4 solution. In study 2 the kinetic parameters of three young peach rootstocks in nutrient solution were determined. Kinetic parameters (Vmax, Km, Cmin, and Influx) and morphological parameters of the peach trees were evaluated. In study 3 we studied the influence of the canopy on the kinetic parameters of N. absorption. For this, peach rootstocks with and without grafting of the cultivar Chimarrita were cultivated in nutrient solution. In study 4, the use of N sources with and without cover crops was evaluated as a management strategy to increase the recovery of N in peach trees. For this, cultivated grafted peach rootstocks were cultivated in pots under greenhouse conditions, submitted to N sources (urea and organic compost), with and without Paspalum notatum. Nutritional, morphological and physiological parameters were evaluated. In study 5, the recovery of N derived from the fertilizer applied in a piecemeal manner and not parceled out in peach trees in production was evaluated. In study 1, it was observed that the depletion of the internal reserves of the peach tree for 30 days in CaSO4 allows determining the kinetic parameters in the peach tree. In study 2 it was observed that the Tsukuba 1 rootstock is more efficient in N uptake in relation to the Aldrighi and Clone 15 rootstocks. In study 3 it was verified that the cultivar scion Chimarrita increased the absorption efficiency of N of the Okinawa rootstock. In study 4, it was observed that fertilization with urea is more efficient, however, the presence of cover crops, in the case of Paspalum notatum, could compete for N, anticipating leaf senescence. In study 5, it was verified that the application of N in a split way in the budding and final flowering periods allows for the greater recovery of N by the peach tree. But most of the N present inside the peach in the year of application of the fertilizer and especially in the year after the application is derived from sources other than fertilizer applied.